Veículos elétricos em órgãos públicos: metodologia para substituição gradual da frota a combustão por veículos elétricos - Thomé, Belisario Antonio (2021)
The market for electric vehicles (EV) in Brazil is still insignificant when compared to the existing fleet in countries in Europe, China and the United States, where there has been significant growth in recent years. Brazil represents an important automotive market, and it could be very significant in what concerns to opportunities for national and foreign investors, if a policy for electric vehicles were planned in the future, considering that one of the limiting factors for the growth of this market is related to the high price of the electric vehicle in the country. In what concerns the acquisition of EV, public agencies have the advantage of tax exemptions, which reduces the acquisition cost and provides significant savings with supply and maintenance when compared to their fleet of vehicles with internal combustion engines, when replaced by electric vehicles. The main motivation for this case study is the opportunity to reduce the fixed expenses of Public Agencies. The feasibility analysis of this case study demonstrates, by comparing combustion and electric vehicles, identifying the elements that can contribute to the decision regarding the replacement of the existing fleet, a significant saving in fuel expenses. The study addresses the case of the vehicle fleet of ALA 4 - Unit of the Air Base of Santa Maria, in which the transition from a fleet powered by internal combustion to an electric one is evaluated, considering only the energy aspects. Based on the data collected from these vehicles in the period from January to December 2019, a comparison between the costs of fueling diesel and gasoline with the costs for recharging the batteries of electric vehicles in the Military Base's electrical network will be presented. Two possibilities for recharging EVs will be presented as well. The first, through the electricity supplied by the Distributor and the second using the energy generated by the photovoltaic plant in the Military Unit. The reduction in expenses with the replacement of the fleet by EV are expressive in both scenarios, compared to the costs of supplying the internal combustion vehicles of the current fleet, with gasoline and diesel.